Immunomodulatory Role of BLG-Derived Peptides Based on Simulated Gastrointestinal Digestion and DC-T Cell from Mice Allergic to Cow’s Milk - Xin Ma; Fan Yang; Xuanyi Meng; Yong Wu; Ping Tong; Jinyan Gao; Hongbing Chen; Xin Li (Foods, 2022)
Peptides, but not whole protein, elicit an allergic reaction since food allergens should be consumed by digestion. In this study, we explored the remaining peptides after simulated digestion of cow’s milk in order to search for β-lactoglobulin (BLG)-derived peptides that could play an immunomodulatory role. As a major allergen in milk, BLG-derived peptides, 109 in total, were identified both from simulated infant and adult digestion in vitro. These peptides were mainly located in four regions, and they were synthesized as five peptides, namely, BLG1–14, BLG24–35, BLG40–60, BLG82–101, and BLG123–139. Then, the effect of peptides on the Caco-2 cell’s transport absorption, the co-stimulatory molecules of DC, and the T-cell phenotype was explored. The results suggested all peptides showed better transport absorption capacity with the apparent permeability coefficient higher than 2 × 10−6 cm·s−1. The ability of BLG40–60 for promoting lamina propria-derived DC cell (LPDC) maturation was observed by the increase in MHC II. Moreover, BLG1–14 and BLG40–60 directed activation of T lymphocytes towards a Th1 phenotype. This is the first report of the immunomodulatory potential of peptides in the sensitization of allergic reaction, and one peptide, BLG40–60, was regarded as an immunomodulatory peptide, one that should be further explored in an animal model in depth.